2020
DOI: 10.1016/j.jelectrocard.2020.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning techniques for detecting electrode misplacement and interchanges when recording ECGs: A systematic review and meta-analysis

Abstract: Introduction: Electrode misplacement and interchange errors are known problems when recording the 12-lead electrocardiogram (ECG). Automatic detection of these errors could play an important role for improving clinical decision making and outcomes in cardiac care. The objectives of this systematic review and meta-analysis is to 1) study the impact of electrode misplacement on ECG signals and ECG interpretation, 2) to determine the most challenging electrode misplacements to detect using machine learning (ML), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…2 . There is an intermediate group including diseases of the circulatory system (N = 9) [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , diseases of the musculoskeletal system (N = 8) [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , diseases of the digestive system (N = 7) [82] , [83] , [84] , [85] , [86] , [87] , [88] and the nervous system (N = 7) [89] , [90] , [91] , [92] , [93] , [94] , [95] . There are a few reviews focused on other categories such as diseases of respiratory system (N = 4) [96] , [97] , [98] , [99] , visual system (N = 3) [100] , [101] , [102] and the other chapters include only one or two systematic reviews [103] , [104] , [105] , [106] , [107] , [108] , [109] , [110] , [111] , [112] , [113] , [114] , [115] , [116] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 . There is an intermediate group including diseases of the circulatory system (N = 9) [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , diseases of the musculoskeletal system (N = 8) [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , diseases of the digestive system (N = 7) [82] , [83] , [84] , [85] , [86] , [87] , [88] and the nervous system (N = 7) [89] , [90] , [91] , [92] , [93] , [94] , [95] . There are a few reviews focused on other categories such as diseases of respiratory system (N = 4) [96] , [97] , [98] , [99] , visual system (N = 3) [100] , [101] , [102] and the other chapters include only one or two systematic reviews [103] , [104] , [105] , [106] , [107] , [108] , [109] , [110] , [111] , [112] , [113] , [114] , [115] , [116] .…”
Section: Resultsmentioning
confidence: 99%
“…The effective management of public health systems is a multifactorial responsibility with a wide range of actors and effects. Like any other medical act, the provision of care services at a populational level involves the screening and diagnosis of certain conditions, the treatment and the follow-up of those conditions [71] , [95] , [115] . In this context, the use of AI has demonstrated that it can provide powerful tools to support and inform decisions and even automate tasks to aid clinicians, epidemiologists and policy makers on the most efficient strategies to promote health at a population level [137] , including the current COVID-19 pandemic [125] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the potential for improving insight and trustworthiness of developed models, these methods may also help determine which signal features are important and explain patterns that are uncovered by the machine learning process. While these methods have demonstrated promising results in the aid of ECG classification (Rjoob K et al, 2020;Jo YY et al, 2021), we could not find any published works on explainable AI methods applied on EDA data at the time of this review.…”
Section: Machine Learningmentioning
confidence: 99%
“…In general, these detection algorithms have had high results for peripheral electrodes; however, inversion detection of precordial electrodes is less accurate, with values ranging from sensitivities of 20% to 99% [11]. The first study that used lead correlation to detect electrode exchanges automatically is that of Jekova [12], which revealed a high correlation between adjacent precordial electrodes that goes in descending order as one moves away towards the other electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Modern methods of interchange detection are based on the use of Machine Learning, as is the use of Decision Trees, Artificial Neural Networks, Amplitude Thresholds, and Support Vector Machines [11]. These methods possess variable and inconsistent Sensitivities (Se) and Specificities (Sp), finding Se = 44.…”
Section: Introductionmentioning
confidence: 99%